2010
DOI: 10.1258/ht.2009.009025
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to therapeutic splint wear in adults with acute upper limb injuries: a systematic review

Abstract: Introduction. Non-adherence with therapeutic splinting in acute hand injury can reduce treatment benefits, increase risk of disability and bias assessment of treatment efficacy. This systematic review aims to critically analyse the literature on splinting of acute upper limb injuries to identify key factors that could influence patient adherence with splint wear. Methods. Trials were identified from searches of EMBASE, MEDLINE, CINAHL (to June 2009) and reference lists of articles and relevant reviews. Search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 43 publications
0
14
1
1
Order By: Relevance
“…Intrinsically, the outcome will be highly dependent on the skills and knowledge of the medical practitioner. Even with highly trained health professionals completing this, there are many factors that impact on the wearing of splints resulting in non-adherence and decreased outcomes[ 3 ]. In addition, it is a lengthy and labor-intensive process requiring the fabrication of multiple casts leading to excessive use of materials and efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsically, the outcome will be highly dependent on the skills and knowledge of the medical practitioner. Even with highly trained health professionals completing this, there are many factors that impact on the wearing of splints resulting in non-adherence and decreased outcomes[ 3 ]. In addition, it is a lengthy and labor-intensive process requiring the fabrication of multiple casts leading to excessive use of materials and efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Although aesthetics was analysed in other studies on hand orthoses ( 8 , 18 ), we are not aware of studies that have reported specifically on the aesthetics of 3D-printed hand orthoses. Considering that patient-reported outcome measures (PROMs), such as aesthetics, are becoming increasingly important ( 19 ), that aesthetics can influence the adherence with wearing an orthosis ( 20 ), and that, with 3D-printing, there are good possibilities to personalize the orthosis, future studies should assess satisfaction with the aesthetics of 3D-printed hand orthoses in a larger population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using interactive tools such as WhatsApp can increase the patients’ performance in the process of rehabilitation. The implementation of educational programs based on burn victims’ needs improves their adherence to the treatment regimen [ 41 ]. Therefore, another potential reason for the positive results obtained in the present study may be the rapid responding to the patients’ real needs by the medical team, since patients could quickly contact the medical team members and receive a proper and prompt response if they faced any issues or ambiguities regarding the rehabilitation exercises.…”
Section: Discussionmentioning
confidence: 99%